Sweet Tooth/ Fathin Liyana Abdul Karim and Nur Hafizatul Hasanah Mohamad Samad - Abdul Karim, Fathin Liyana; Mohamad Samad, Nur Hafizatul Hasanah (2022)
“Sweet Tooth” is the partnership business that was established in March 2022 with the dream of bringing happiness and satisfaction to our customers when they taste our brownis chips cookies. We decided to run this business because nowadays cookies have become a popular snack among young people. The objective of our business is to offer good quality snacks with a variety of flavor and create the best memorable experience for everyone who has eaten our brownis chips cookies . We are also dreaming of becoming one of the top brands of cookies business in Malaysia. The reason we came up with the idea of a brownis chips cookies is because we want to provide the customer the best snacks that they can have as their breakfast, lunch or dinner. We choose Facebook as our main social platform for “Sweet Tooth” because Facebook Page has the potential to help us in advertising our business. Facebook is a low-cost marketing method that is particularly beneficial to small businesses that are just getting started. Second, because Facebook has the greatest user base, entrepreneurs may use it to discover their target demographic. Finally, existing and potential consumers who like our page on Facebook can enhance brand recognition, which will eventually lead to more people learning about our business. “Sweet Tooth” frequently posts hard sale and soft sell posts on their Facebook page in order to engage with people and to entice them to purchase sweet and crunchy brownies chips. The pricing of the cookies is RM15 each.